ICBT in routine care: A descriptive analysis of successful clinics in five countries - Titov, Nickolai; Dear, Blake; Nielssen, Olav; Staples, Lauren; Hadjistavropoulos, Heather; Nugent, Marcie; Adlam, Kelly; Nordgreen, Tine; Bruvik, Kristin Hogstad; Hovland, Anders; Repål, Arne; Mathiasen, Kim; et al. (Internet interventions : the application of information technology in mental and behavioural health, 2018)
Clinical trials have demonstrated the efficacy of internet delivered cognitive behaviour therapy (ICBT) for anxiety and depression. However, relatively little is known about the context, operations, and outcomes of ICBT when administered as part of routine care. This paper describes the setting, relationship to existing health services, procedures for referral, assessment, treatment, patients and outcomes of ICBT clinics in Sweden, Denmark, Norway, Canada and Australia. All five clinics provide services free or at low cost to patients. All have systems of governance to monitor quality of care, patient safety, therapist performance and data security. All five clinics include initial assessments by clinicians and between 10 and 20 min of therapist support during each week. Published reports of outcomes all demonstrate large clinical improvement, low rates of deterioration, and high levels of patient satisfaction. Services that require a face to face assessment treat smaller numbers of patients and have fewer patients from remote locations. The paper shows that therapist-guided ICBT can be a valuable part of mental health services for anxiety and depression. Important components of successful ICBT services are rigorous governance to maintain a high standard of clinical care, and the measurement and reporting of outcomes. •This study describes internet-delivered cognitive behaviour therapy (ICBT) in routine care in five high income countries•Each service uses a comprehensive framework of policies and procedures to ensure patient safety, data safety, and service quality•Each clinic measures outcomes to monitor progress and safety, and demonstrate the effectiveness of ICBT in routine care•The provision of these services within public health systems enables services to be offered free or at low cost•High quality ICBT can be tailored to local contexts and delivered to a large number of patients in routine clinical care